Ictiofauna do semi-árido potiguar, Nordeste do Brasil: composição, riqueza e ecologia reprodutiva de espécies endêmicas - Souza, Liliane de Lima Gurgel (2010)
Understanding the factors related to the reproductive strategy of endemic fish species at spatial and a temporal scale is essential for their conservation and management. The present study investigated the reproductive strategy of Prochilodus brevis and Cichlasoma orientale in the River Assu, located in the semi-arid Northeastern Brazil. Population structure, sex proportion, length at first maturity, stages of gonadal development, gonadosomatic index, condition factor, reproductive period and limnological variables were determined. Temporal distribution of mean rainfall, water temperature, dissolved oxygen concentration, pH and electrical conductivity values were related to the reproductive period of P. brevis and C. orientale. The present study deals with the composition, species richness and endemism in fish species of River Assu. Analyses of GSI, K and size of oocytes indicate the reproduction of P. brevis occurs from January to March and that this species is a total spawner. Rainfall influenced alterations in limnological characteristics and the reproductive period of this species. The reproductive strategy of P. brevis is well adapted to the environmental characteristics of the semi-arid region. Cichlasoma orientale is a batch spawner with a reproductive period between the months March to June and in September, with a reproductive peak in the beginning of the rainy season. Multiple spawnings in one breeding season indicate that C. orientale is well adapted to the environmental characteristics of the semi-arid region. A total of 556 individuals were captured which were distributed in 3 orders, 10 families and 17 species, of which, 13 were endemic, 4 introduzed and one exotic. The orders more representatives in terms of number of fish species were Characiformes, Perciformes and Siluriformes. Among the families, Prochilodontidae was dominant followed by Cichlidae. P. brevis, an endemic species was most expressive followed by Trachelyopterus galeatus. Nine species were considered constant, five accessories and three accidental. The results demonstrate an elevated number of endemic species, among them the rheophilic fish which migrate to the head river to spawn, and a reduced number of introduced species. The presence of endemic species increases the importance of conservation and adequate management practice of this natural semi-arid ecosystem.